Seyahat Acenteleri Tarafından Yurtiçi Paket Turlarda Uygulanan Satış Teknikleri Üzerine Bir Araştırma, İstanbul İli Örneği - Cansu, Emrullah; Bahadır, Uğur (Turk Turizm Arastirmalari Dergisi, 2019)
For the purpose of profit, commercial organizations that provide tourist accommodation services, transportation, sightseeing, sports, entertainment etc. services, tourism information services, and at the same time marketing services of their own or other companies are called travel agencies. Travel agencies offer many products and services such as package tours to the consumer. Package tours are contracts that include services such as transportation, accommodation and are sold at a single price that includes all facilities, with at least 1-night accommodation. Package tours are considered one of the most important sources of income for travel agencies. For this reason, the use of effective techniques in the sale of these tours is important in terms of increasing these incomes. In this direction, it is the purpose of this work to reveal the techniques applied in the sales of package tours in travel agencies, to identify the problems experienced in this issue and to find solutions, and then to present a projection for the development of new techniques that can be applied in package tour sales. Interviewing and observation techniques, which are qualitative data collection methods, were used in the study. As a result, it has been determined that various opportunities and campaigns have been applied to put the trust in the customers at the forefront. In addition, it was found that it provided more participants in the tours where the opportunity to show different places.
Keywords: Turizm; Seyahat Acentesi; Paket Tur